Psychometric properties of self-reported financial toxicity measures in cancer survivors: a systematic review - Yan Hu; Zheng Zhu; Weijie Xing; Lucylynn Lizarondo; Jian Peng; Huan Wen; Yanling Sun; Winnie K W So (BMJ Open)
Objective The aim of this systematic review was to summarise the psychometric properties of patient-reported outcome measures (PROMs) measuring financial toxicity (FT) in cancer survivors.Design This systematic review was conducted according to the guidance of the Consensus-Based Standards for the Selection of Health Measurement Instruments (COSMIN) methodology.Data sources Comprehensive searches were performed in PubMed, MEDLINE, Embase, CINAHL, PsycINFO, Web of Science, ProQuest and Cochrane Library from database inception to February 2022.Eligibility criteria for selecting studies We included studies that reported any PROMs for measuring FT in cancer survivors who were ≥18 years old. FT was defined as perceived subjective financial distress resulting from objective financial burden. Studies that were not validation studies and that used a PROM only as an outcome measurement were excluded.Data extraction and synthesis Two reviewers independently extracted data from the included papers. We used the COSMIN criteria to summarise and evaluate the psychometric properties of each study regarding structural validity, internal consistency, reliability, measurement error, hypothesis testing for construct validity, cross-cultural validity/measurement invariance, criterion validity and responsiveness.Results A total of 23 articles (21 PROMs) were eligible for inclusion in this study. The findings highlighted that the Comprehensive Score for Financial Toxicity (COST) had an adequate development process and showed better psychometric properties than other PROMs, especially in internal consistency (Cronbach’s α=0.92), reliability (intraclass correlation coefficient=0.80) and hypothesis testing (r=0.42–0.20).Conclusions From a psychometric property perspective, the COST could be recommended as the most suitable worldwide available measure for use in research and clinical practice across different contexts. We suggest that PROMs should be selected only after careful consideration of the local socioeconomic context. Future studies are warranted to develop various FT PROMs based on different social and cultural backgrounds and to clarify the theoretical grounds for assessing FT.